Financial uncertainty of a startup - G. R. Yusupova; E. I. Nesmeyanova (Вестник университета)
This article discusses the transformation of   the system of   attracting investments in  startups. The process of   finding an  investor for a   startup has had a   difficult path of  formation in   recent years. An  entrepreneur’s interest in   different sources of   investment is  associated with determining their possibilities for implementing the chosen business idea. For various purposes, businesses need different types of  investments: loans, credits, sale of   shares or   stocks. The search for an   investor for a   startup and their attraction is   associated with specific requirements for an  entrepreneur, which are practically not written about in  the media and advertised. The article focuses on   the types of   finance involved in   business. The issues of  the difference between grant financing of a   startup and the process of   searching and attracting an   investor are raised, since the requirements from the grantee fundamentally change the requirements for specialists who should be  involved in   the work and the requirements for maintaining the financial stability of  an organisation. The authors also consider the professional platforms for investors that have developed in   Russia and the forms of   investment relations: in   exchange for receiving a   share of   profits; in   exchange for a   share of   the proceeds.